Simulação computacional do efeito da pressão sobre a enzima pectina metilesterase do tomate - Trindade, Lucas Carvalho (2018)
This work describes a computer simulation developed by means of the GROMACS suit of program. More specifically, we studied how the computational simulation evaluated the evolution of the radius of gyrate of the Pectin Methylesterase (PME) protein of tomato as a function of the applied pressure under a constant temperature. It was made a description of the physical models used by the program. In addiction, it were briefly described characteristics of amino acid, protein systems, and structures. The computational simulations considered a temperature of 26.85oC and pressures applied of 1 bar, 1 kbar, 3 kbar, 5 kbar, 7 kbar, 9 kbar and 10 kbar. The simulations worked a pressure action time of 100 peak seconds. The results of the simulation indicated a nonlinear reduction of the radius of gyrate of the Pectin Methylesterase (PME) enzyme according to the rise in pressure applied, considering a fixed temperature.